The prevalence of congenital heart disease in newborn detected by pulse oximeter screening test at 24 hours of birth and its correlation with clinical findings and ECHO - Suresh, Vindhya; Mysore Ramraj, Savitha (International Journal of Contemporary Pediatrics, 2024)
Background: Detecting congenital heart disease (CHD) early is crucial for better outcomes, but most newborns show no symptoms. Newborn screening for CHD can identify such cases preventing serious consequences. This study aims to determine CHD prevalence and evaluate the effectiveness of pulse oximeter screening and clinical examination, correlating them with echocardiography findings. Methods: A cross-sectional study was conducted to screen for CHD in all newborns born in our institution over a period of 3 months. A sample of 660 newborns were screened by pulse oximeter screening and clinical examination after random sampling. Results: Comparison of baseline data like age distribution in mothers, gender and gestational age were comparable between newborns with CHD and those without CHD. A total of 8 CHDs were picked up after screening 660 newborns screened during a period of 3 months. CHDs that were picked up included hypoplastic left heart syndrome, pulmonary atresia, bicuspid aortic valve, transposition of great arteries, coarctation of the aorta, and other complex CHDs. It was found that either clinical examination or pulse oximeter screening has higher sensitivity than pulse oximetry screening or clinical examination alone. Conclusions: For identification of a CHD in newborns after 24 hours of birth the order of preference for screening based on sensitivity is as follows-either pulse oximeter screening or clinical examination >clinical examination >pulse oximeter screening >pulse oximeter screening and clinical examination.